CASE REPORT: LIVER CIRRHOSIS - Aditya Saskara, Pande Made; Suryadarma, IGA (E-Jurnal Medika Udayana; vol 2 no4 (2013):e-jurnal medika udayana, 2013)
Liver cirrhosis is a state of the accumulation of extracellular matrix or scar tissue in response to acute or chronic liver injury. The causes are varied, but the majority of patients with chronic liver disease caused by a virus or drinking alcohol. Liver cirrhosis often occur without symptoms and found during routine examination, but in advanced complications such as liver failure and portal hypertension can arise. Therapy in patients with liver cirrhosis aims to reduce the progression of diseases such as prevent further liver damage, prevention, and complications management.
Keywords: : liver cirrhosis, liver failure, portal hypertension